Gatotkaca's Birth Story As A First Step To Introduce Children With Puppets - Leocadia Desy Pranatalisa; Ridwan Sanjaya; Alb. Dwiyoga Widiantoro (Soegijapranata Catholic University, 2015)
Puppet is most prominent one of the arts in Indonesia. In the puppet also has good values delivered. In an educational pursuit puppet story are characters that are also included in the 18-character value that has been determined by the curriculum in 2013 as efforts to establish the desired character of the nation and the State.Although the puppet contains good values that can be emulated, unfortunately generation of young people today just do not know the puppet. This is influenced by the development of technology that can not only be used to help complete the work, but also as a means of entertainment. This makes the younger generation today is more interested in the development of the technology to get to know about puppet.To introduce the puppets against children, can be done by introducing one puppet stories. The story introduced should also start from scratch a puppet story. It is expected with the introduction of one of the stories of the many stories puppet, can make children interested in puppets and imitating good attitude conveyed in the story. Stories that can be used for the initial introduction of the puppet is a story about the birth of Gatotkaca. This is because many know about the characters Gatotkaca therefore begins with the initial story of his birth. From the story of the birth Gatotkaca there are also many good things delivered and there are also other figures like clown is widely known. It is expected to also be able to facilitate the children to get to know the story because there are already several characters they know.